Patient satisfaction with root canal treatment and outcomes in the Swedish public dental health service: A prospective cohort study. (27th July 2021) - Wigsten, Emma; Al Hajj, Amenah; Jonasson, Peter; Kvist, Thomas
Abstract: Aim: To document satisfaction with root canal treatment procedures and outcomes among patients treated at Swedish public dental clinics. Method: The original material comprised 243 patients who began root canal treatment (RCT) at 20 public dental clinics in the county of Västra Götaland, Sweden. One to three years later, 236 (97.1%) were posted a questionnaire of eight items, rating patient perceptions of RCT completion, present pain intensity and satisfaction with the RCT. To evaluate the reliability of the original responses, the first 50 respondents were mailed a follow‐up questionnaire. Both descriptive and analytical statistics were used to compare respondents and nonrespondents and tooth groups. Results: One hundred and fifty‐nine patients (67.4%) responded: 86 (54.1%) women and 73 (45.9%) men. The mean age 52.5 years, was higher than for nonrespondents ( p < .001). A completed root filling was registered for the majority of the teeth ( n = 112, 70.9%), but significantly fewer molars had been completed ( n = 46, 59.7%, p = .02). Fifty per cent ( n = 59) of the patients reported current pain, mostly mild in intensity ( n = 45, 38.1%). One hundred and twenty‐three patients (80.9%) recalled experiencing pain during RCT. The highest satisfaction was registered for the item 'chewing ability' (mean = 1.6, SD = 1.9). The majority of patients ( n = 114, 75.0%) stated that in retrospect they would still have chosen RCT. However, these patients belonged to the group which either registered the tooth as still present or had not experienced much discomfort during or after RCT. Forty‐four patients (88.0%) responded to the second questionnaire. The reliability of the responses was good. In summary, one to 3 years after beginning RCT at a public dental clinic, patient satisfaction was high, even though every fourth molar had been extracted or treatment had not been completed and half the patients reported persistent pain. The reliability of the patients' responses was considered to be good. Conclusions: The results indicate a need for further clinical observational studies of RCTs undertaken in general dental practice, with special reference to patient‐centred outcomes.